Revisiting differential control of sympathetic outflow by the rostral ventrolateral medulla - Kulkarni, Soumya S.; Mischel, Nicholas A.; Mueller, Patrick J. (Frontiers in Physiology, 2023)
The rostral ventrolateral medulla (RVLM) is an important brain region involved in both resting and reflex regulation of the sympathetic nervous system. Anatomical evidence suggests that as a bilateral structure, each RVLM innervate sympathetic preganglionic neurons (SPNs) on both sides of the spinal cord. However, the functional importance of ipsilateral versus contralateral projections from the RVLM is lacking. Similarly, during hypotension, the RVLM is believed to rely primarily on withdrawal of tonic GABAergic inhibition to increase sympathetic outflow but whether GABA withdrawal mediates increased activity of functionally different sympathetic nerves is unknown. We sought to test the hypothesis that activation of the ipsilateral versus contralateral RVLM produces differential increases in splanchnic (SpSNA) versus adrenal (AdSNA) sympathetic nerve activities, as representative examples of functional different sympathetic nerves. We also tested whether GABA withdrawal is responsible for hypotension-induced increases in SpSNA and AdSNA. To test our hypothesis, we measured AdSNA and SpSNA simultaneously in Inactin-anesthetized, male Sprague-Dawley rats during ipsilateral or contralateral glutamatergic activation of the RVLM. We also produced hypotension (sodium nitroprusside, i.v.) before and after bilateral blockade of GABAA receptors in the RVLM (bicuculline, 5mM 90nL). Glutamate (100 mM, 30nL) injected into the ipsilateral or contralateral RVLM produced equivalent increases in SpSNA, but increased AdSNA by more than double with ipsilateral injections versus contralateral injections (p<0.05; n=6). In response to hypotension, increases in AdSNA were similar after bicuculline (p>0.05), but SpSNA responses were eliminated (p<0.05; n=4). These results provide the first functional evidence that the RVLM has predominantly ipsilateral innervation of adrenal nerves. In addition, baroreflex-mediated increases in SpSNA but not AdSNA are mediated by GABAA receptors in the RVLM. Our studies provide a deeper understanding of neural control of sympathetic regulation and insight towards novel treatments for cardiovascular disease involving sympathetic nervous system dysregulation.